Wired to create : unraveling the mysteries of the creative mind - Kaufman, Scott Barry, 1979-; Gregoire, Carolyn (Perigee, an imprint of Penguin Random House LLC, 2015)
"Is it possible to make sense of something as elusive as creativity? Based on psychologist Scott Barry Kaufman's groundbreaking research and Carolyn Gregoire's popular article in the Huffington Post, Wired to Create offers a glimpse inside the "messy minds" of highly creative people. Revealing the latest findings in neuroscience and psychology, along with engaging examples of artists and innovators throughout history, the book shines a light on the practices and habits of mind that promote creative thinking. Kaufman and Gregoire untangle a series of paradoxes-- like mindfulness and daydreaming, seriousness and play, openness and sensitivity, and solitude and collaboration - to show that it is by embracing our own contradictions that we are able to tap into our deepest creativity. Each chapter explores one of the ten attributes and habits of highly creative people: Imaginative Play * Passion * Daydreaming * Solitude * Intuition * Openness to Experience * Mindfulness * Sensitivity * Turning Adversity into Advantage * Thinking Differently With insights from the work and lives of Pablo Picasso, Frida Kahlo, Marcel Proust, David Foster Wallace, Thomas Edison, Josephine Baker, John Lennon, Michael Jackson, musician Thom Yorke, chess champion Josh Waitzkin, video-game designer Shigeru Miyamoto, and many other creative luminaries, Wired to Create helps us better understand creativity - and shows us how to enrich this essential aspect of our lives. "--